MENINJAU STRATEGI KEPENGAWASAN DALAM MENINGKATKAN AKUNTABILITAS DAN TRANSPARANSI TATA KELOLA PENDIDIKAN - Shelty D. Sumual; Bella Felicita Rambitani; Marisca Sadsuitubun; Neiles Wakur; Syerri Yullita Sumual (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Education plays an important role in the development of society. Effective, accountable, and transparent education governance is needed to ensure the realization of quality education. This article reviews supervisory strategies as an effort to increase accountability and transparency in education governance. Through literature review and expert opinion, this article investigates the role of oversight in ensuring compliance with education policies, efficient use of resources, and monitoring the performance of educational institutions. In addition, the close relationship between supervision, accountability, and transparency is also detailed, where effective supervision helps strengthen accountability and build transparency in education governance. The practical implications of this research include: There is a need for the implementation of targeted supervisory strategies. Capacity building of supervisory agencies. Strengthening interagency cooperation to achieve the goals of accountability and transparency in education governance. Thus, this article contributes to understanding supervision's role in improving educational governance's effectiveness.